Moments of Critical Self-Reflection of a Transformative Mathematics Teacher - Luitel, Laxman (Journal of Transformative Praxis, 2020)
I have been travelling through a transformative research journey since the beginning of my MPhil study. It allows me to understand my past and present strengths and limitations in learning and teaching of mathematics, thereby envisaging alternative practices for futurist education. As my research involved critical self-reflection on my professional praxis, I used a multi-paradigmatic (interpretivism, criticalism, postmodernism) research approach and autoethnography as a research methodology. Thus, the main purpose of the paper is to portray the moments of critical self-reflection on my experiences of doing mathematical activities during my childhood and learning mathematics during my early days of schooling, aiming at improving my practices as a teacher, a practitioner-researcher and an educator. I used Habermasian knowledge constitutive interests (i.e., technical, practical, and emancipatory) and Schubert’s curriculum images (i.e., content or subject matter, experiences, cultural reproduction, etc.) to interrogate my experiences of doing and learning mathematics. As a mathematics teacher and practitioner-researcher, reflections on my childhood experiences as well as early days of schooling ultimately opened up somewhat closed box of my personal and professional practices. This paper in/directly indicates the enhancement of the students’ engagement in mathematics through context-based activities. Moreover, the selection of the contents should be based on learners’ experiences which might be experienced through mathematically rich activities such as games, daily household works, etc.